Innovation of Elephant Ginger Juice (Zingiber officinale var. Officinarum) on Physicochemical and Sensory Properties of Ginger Milk Curd Product Manufacturing - Suharto, El Latifa Sri; Juliyarsi, Indri; Miftahul Jannah, Frista (Faculty of Animal Science Universitas Brawijaya, 2025)
This study aimed to determine the effect of adding elephant ginger (Zingiber officinale var. Officinarum) juice at different concentrations on ginger milk curd's yield, protein content, and sensory characteristics. This study used 10.000 mL of fresh FH cow's milk, 8.000 g of elephant ginger and 1.000 g of sugar. The method used was a Randomised Block Design with 4 treatments and 5 replications. The treatment in this study was the addition of elephant ginger juice to ginger milk curd as P1 (15%), P2 (20%), P3 (25%) and P4 (30%). The variables observed were yield, protein content and sensory. Based on the research conducted, the results showed that the addition of elephant ginger juice has no significant effect (p > 0.05) on yield, but has a significant effect (p < 0.05) on protein content and sensory values, namely colour, texture, taste and aroma of ginger milk curd. The results of the concentration with the best percentage of addition of elephant ginger juice in the production of ginger milk curd are found in treatment P1 (15%) with a yield value of 77.59%, protein content of 6.10%, sensory colour 3.96 (like), sensory texture 3.90 (like), sensory taste 3.66 (like) and sensory aroma 3.84 (like). In accordance with the conclusions of the research conducted, the author proposes that future studies consider adding only 15-25% elephant ginger juice to ginger milk curd, as this proportion was found to be more preferred by the panelists.